Vitamin D and Lipid Profiles in Postmenopausal Women: A Meta-Analysis and Systematic Review of Randomized Controlled Trials - Liu, Weiting; Wu, Zezhen; Zhu, Dan; Chen, Genben; Yan, Guiming; Zhang, Shuo; Chen, Fengwu; Khan, Barkat Ali; Hou, Kaijian (Frontiers in Molecular Biosciences, 2021)
Background and aim: It is known that hyperlipidemia and low vitamin D level are risk factors associated with cardiovascular disease (CVD). However, the effect of vitamin D administration on lipid profiles of postmenopausal women remains unclear. This study aims to evaluate the effect of vitamin D on lipid profiles in postmenopausal women based on meta-analysis and systemic review. Methods: The literature search was performed in multiple databases (Scopus, PubMed/Medline, Web of Science, and Embase)from 1997 up to 1 May 2021. The statistical analysis was performed using the Stata software version 14 (Stata Corp. College Station, Texas, USA). The effects of vitamin D administration of the lipid profiles, including Triacylglycerol (TG), LDL-Cholesterol(LDL-C), HDL-Cholesterol (HDL-C) and Total Cholesterol( TC) were evaluated by the Der Simonian and Laird random effects model. The weighted mean difference (WMD) and 95% confidence intervals (CI) were calculated. Results: The level of TG changed significantly by -3.76 mg/dL (CI: -6.12 to -1.39, P=0.000) and HDL-C by 0.48 mg/dL (CI: -0.80 to -0.15, P=0.004) in vitamin D administration group (11 eligible trials (placebo=505 participants, vitamin D intervention=604 participants)) compared to the control group in the postmenopausal women. . Taking into account this comparison between groups, in contrast, the level of LDL-Cholesterol(LDL-C) (WMD: 0.73 mg/dL, 95% CI: -1.88, 3.36, p = 0.583) and TC (WMD: 0.689 mg/dL, CI: -3.059 to 4.438, P=0.719) did not change significantly. Conclusions: In conclusion, the postmenopausal women vitamin D administration decreased the concentrations of TG and HDL-C, but not of LDL-C and TC.